Collaborative Marketing and Online Purchase Behaviour of Consumers in South-South Nigeria (UNIZIK Journal of Marketing, 2024)
This present study examined the empirical link between collaborative marketing and online purchase behaviour of consumers in South-South, Nigeria. The study adopted cross-sectional survey and correlation designs. The study employed cluster sampling to survey 400 active online consumers at Jumia and Konga collection centers in South-South Nigeria. The questionnaire was used as source of primary data to elicit response from the participants. The Spearman Rank Order Correlation Coefficient statistical tool was employed for the bivariate analysis to test the three hypotheses. The findings revealed that information sharing, content sharing, and personalization significantly influence online purchase behaviour of consumers in a positive way. Based on the findings, the study concludes that collaborative marketing increases online purchase behaviour of consumers in South-South, Nigeria, through information sharing, content sharing and personalization. Therefore, the study recommends that e-retailers should incentivize online consumers to encourage them to make brand reviews, recommendations and ratings regarding their shopping experience, since consumers cannot physically feel or touch the product to ascertain its quality. Finally, e-retailers should strive to personalize shopping experience with relevant product suggestions, targeted offers, personalized messages like gratitude to customers, birthday or special event messages as a way of strengthening brand relationship
Keywords: Collaborative marketing; information sharing; content sharing; personalization; online purchase behaviour